2013
DOI: 10.1111/1744-7917.12044
|View full text |Cite
|
Sign up to set email alerts
|

Tier‐1 assays for assessing the toxicity of insecticidal proteins produced by genetically engineered plants to non‐target arthropods

Abstract: In assessing an insect-resistant genetically engineered (IRGE) crop before its commercialization, researchers normally use so-called "Tier-1 assays" as the initial step to determine the effects of the crop on non-target organisms. In these tests, the insecticidal proteins (IPs) produced by the IRGEs are added to the diets of test organisms in the laboratory. Test organisms in such assays can be directly exposed to much higher concentrations of the test IPs than they would encounter in the field. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 50 publications
3
48
0
Order By: Relevance
“…When researchers measure the hazard of an insecticidal compound to a non‐target organism in a dietary exposure assay, they must confirm the concentration, stability and bioactivity of the test compound in the food source, and also confirm the uptake of the compound by the test organism (Romeis et al ., ; Raybould et al ., ; Romeis et al ., ; Li et al ., ). In our study, ELISA measurements showed that the Cry1Ac toxin concentrations in an artificial diet were relatively stable, with 29.6% degradation occurring during the 2‐day feeding exposure.…”
Section: Discussionmentioning
confidence: 97%
“…When researchers measure the hazard of an insecticidal compound to a non‐target organism in a dietary exposure assay, they must confirm the concentration, stability and bioactivity of the test compound in the food source, and also confirm the uptake of the compound by the test organism (Romeis et al ., ; Raybould et al ., ; Romeis et al ., ; Li et al ., ). In our study, ELISA measurements showed that the Cry1Ac toxin concentrations in an artificial diet were relatively stable, with 29.6% degradation occurring during the 2‐day feeding exposure.…”
Section: Discussionmentioning
confidence: 97%
“…In sensitive-insect bioassays, neonate larvae of C. suppressalis were fed for 7 d with artificial diet containing a range of Cry protein concentrations. The EC 50 (toxin concentration resulting in 50% weight reduction compared to the control) was 18 ng/mL diet for Cry1C [25] and 1310 ng/mL diet for Cry2A [12]. Previous research has demonstrated that different Cry proteins can have significantly different insecticidal spectra even if they have high homology.…”
Section: Discussionmentioning
confidence: 97%
“…To identify the potential toxicity of insecticidal proteins produced by novel insecticidal genes or by the insect‐resistant GE plants to target or non‐target insects, dietary exposure systems are necessary. Ideally, artificial diets should be available in which the insecticidal compound can be directly provided to the test species (Romeis et al ., ; Li et al ., , ). In summary, the diet should meet the following requirements: (i) it should be readily accepted by the test species, and efficient for sustaining their normal survival and development; (ii) the test compounds can be readily and uniformly incorporated into the diet; and (iii) the bioactivity of test substance should be maintained during the feeding exposure duration (Li et al ., , ).…”
Section: Discussionmentioning
confidence: 99%